2003
DOI: 10.1074/jbc.m208787200
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-coupled Receptor Kinase 2/Gαq/11 Interaction

Abstract: G protein-coupled receptors (GPCRs) transduce cellular signals from hormones, neurotransmitters, light, and odorants by activating heterotrimeric guanine nucleotide-binding (G) proteins. For many GPCRs, short term regulation is initiated by agonist-dependent phosphorylation by GPCR kinases (GRKs), such as GRK2, resulting in G protein/receptor uncoupling. GRK2 also regulates signaling by binding G␣ q/ll and inhibiting G␣ q stimulation of the effector phospholipase C␤. The binding site for G␣ q/ll resides within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 69 publications
(77 reference statements)
3
87
0
Order By: Relevance
“…DISCUSSION We have previously shown using the IP 3 biosensor eGFP-PH PLC␦ that expression of GRK2 in hippocampal neurons leads to an almost complete suppression of M 1 mACh receptor-mediated IP 3 signaling and that this suppression is independent of kinase activity, because the catalytically inactive K220R GRK2 mutant also completely inhibited signaling (18). In common with a number of other groups (14,15,19,21), we proposed that the suppression of signaling is a consequence of the direct interaction of the N-terminal RH domain of GRK2 with GTPbound G␣ q/11 . In the present study we have examined whether the catalytic activity of GRK2 acts as an alternative or additional mechanism for GRK2-mediated suppression of M 1 mACh receptor signaling.…”
Section: Fig 4 Effect Of Non-g␣mentioning
confidence: 76%
See 3 more Smart Citations
“…DISCUSSION We have previously shown using the IP 3 biosensor eGFP-PH PLC␦ that expression of GRK2 in hippocampal neurons leads to an almost complete suppression of M 1 mACh receptor-mediated IP 3 signaling and that this suppression is independent of kinase activity, because the catalytically inactive K220R GRK2 mutant also completely inhibited signaling (18). In common with a number of other groups (14,15,19,21), we proposed that the suppression of signaling is a consequence of the direct interaction of the N-terminal RH domain of GRK2 with GTPbound G␣ q/11 . In the present study we have examined whether the catalytic activity of GRK2 acts as an alternative or additional mechanism for GRK2-mediated suppression of M 1 mACh receptor signaling.…”
Section: Fig 4 Effect Of Non-g␣mentioning
confidence: 76%
“…To determine whether GRK2-mediated receptor phosphorylation is required for M 1 mACh receptor desensitization, we introduced a single point mutation D110A to create both GRK2 and K220R GRK2 mutants, which are incapable of binding G␣ q/11 (19). When transiently transfected, expression levels of the GRK2, D110A GRK2, K220R GRK2, and D110A,K220R GRK2 constructs were similar in HEK293 cells (data not shown).…”
Section: Suppression Of Grk2 Expression Using An Antisense Grk2mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the a 13 / p115RhoGEF pair is not the only case in which a Gly to Ser mutation at this Ga position fails to affect the interaction; a recent report demonstrated that such a Gly to Ser mutant of a q , a q G188S, retains interaction with the RH domain of GRK2 even though it loses interaction with RGS2 (Sterne-Marr et al, 2003).…”
Section: Discussionmentioning
confidence: 99%